2007
DOI: 10.1080/15287390701252725
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Paraoxonase 192/55 Polymorphism in an Iranian Population

Abstract: Paraoxonase (PON1) is a serum enzyme that plays an important role in prevention of atherosclerosis and also protects against organophosphate-induced neurotoxicity. PON1 displays a high variability in human populations. In this study, PON1-192 and -55 polymorphisms and correlation to serum PON1 activity were investigated in 132 healthy Iranian individuals from Isfahan province. The genotype frequencies for PON1-192 were approximately 48% (QQ), 42.% (QR), and 10% (RR) and for PON1-55 17% (MM), 48% (ML), and 35% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 26 publications
3
7
0
5
Order By: Relevance
“…39,[54][55][56][57] In this study, a wide variation in PON1 activity among individuals was observed; a variability of 6.17-fold was observed when phenylacetate was used as a substrate, and a 4.4-fold variability was observed with substrate CMPA. Although a large interindividual variation in PON1 activity was observed in this work, there is actually less variation in this indigenous population compared with others.…”
Section: Phenotype and Genotype Of Pon1mentioning
confidence: 83%
“…39,[54][55][56][57] In this study, a wide variation in PON1 activity among individuals was observed; a variability of 6.17-fold was observed when phenylacetate was used as a substrate, and a 4.4-fold variability was observed with substrate CMPA. Although a large interindividual variation in PON1 activity was observed in this work, there is actually less variation in this indigenous population compared with others.…”
Section: Phenotype and Genotype Of Pon1mentioning
confidence: 83%
“…The activity of the enzyme is usually measured with paraoxon as a substrate (paraoxonase activity) to characterize its antioxidant capacity; and with phenyl acetate (arylesterase activity) which is considered to correlate with its serum level [26,27]. It has been proposed that paraoxonase proteins including PON1 primarily possess lactonase activity.…”
Section: Discussionmentioning
confidence: 99%
“…O substrato paroxon é eficientemente hidrolisado pela aloenzima 192R (Li et al, 2000;Draganov e La Du, 2004) e outros substratos como soman, sarin e diazoxon são mais rapidamente hidrolisados pela aloenzima 192Q (Humbert et al, 1993;Richter et al, 2009). A isoforma 192Q, in vitro, promove melhor proteção da LDL contra o acúmulo de peróxidos lipídicos Sepahvand et al, 2007) em detrimento da isoforma 192R, a qual, por sua vez, tem sido considerada um fator de risco independente e positivamente associada com a doença coronariana, devido a menor eficácia antioxidativa (Sanghera et al, 1997;Mackness et al,1998;Pérez-Herrera et al, 2008;Vaisi-Raygani et al, 2011).…”
Section: Pon1 E Hdlunclassified
“…O alelo 192Q, no gene da PON1, parece ser mais frequente na população asiática, quando comparado ao alelo 192R (Phuntuwate et al, 2005;Sepahvand et al, 2007;Ozturk et al, 2009;VaisiRaygani et al, 2011), assim como em regiões temperadas da Europa e da América do Norte (Deakin et al, 2003;Hernandez et al, 2003). Achados similares foram também encontrados em alguns estudos realizados na América do Sul (Gamboa et al, 2006;Santos et al, 2005;Maselli, 2007;Pérez-Herrera et al, 2008).…”
Section: Pon1 E Hdlunclassified
See 1 more Smart Citation